2024
DOI: 10.1108/jmp-05-2022-0217
|View full text |Cite
|
Sign up to set email alerts
|

True knowledge vs empowering knowledge: conceptualizing a theory of mindfulness and knowledge transfer (TMKT)

Abraham Cyril Issac,
Amandeep Dhir,
Michael Christofi

Abstract: PurposeMindfulness is the human ability to be fully present, aware of where we are and what we're doing. This study explores on the impact of mindfulness on different elements of knowledge management, knowledge creation, knowledge sharing and knowledge hiding.Design/methodology/approachThe authors undertake an inductive reasoning approach whereby they try to generate themes from specific observations and conceptualize the theory of mindfulness and knowledge transfer.FindingsThis study finds out that mindfulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 109 publications
1
6
0
Order By: Relevance
“…We propose that while the modern pressures to optimize time and efficiency can enhance the happiness of existing stakeholders (Lee et al, 2021), they also promote counterproductive knowledge behaviors (Hammoda and Durst, 2022;Karamitri et al, 2017) Furthermore, our data revealed an indirect but meaningful link between a competitive environment and knowledge sharing, prompting caution when evaluating the vital role of knowledge sharing in workplace happiness (H10). Supporting this, the positive effect of knowledge sharing on psychological outcomes tied to workplace happiness aligns with recent suggestions of using knowledge as an empowering tool among knowledge workers (Issac et al, 2024). In addition, our findings lend weight to arguments around the impact of team interdependence and cultural complexity in healthcare organizations.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We propose that while the modern pressures to optimize time and efficiency can enhance the happiness of existing stakeholders (Lee et al, 2021), they also promote counterproductive knowledge behaviors (Hammoda and Durst, 2022;Karamitri et al, 2017) Furthermore, our data revealed an indirect but meaningful link between a competitive environment and knowledge sharing, prompting caution when evaluating the vital role of knowledge sharing in workplace happiness (H10). Supporting this, the positive effect of knowledge sharing on psychological outcomes tied to workplace happiness aligns with recent suggestions of using knowledge as an empowering tool among knowledge workers (Issac et al, 2024). In addition, our findings lend weight to arguments around the impact of team interdependence and cultural complexity in healthcare organizations.…”
Section: Discussionsupporting
confidence: 88%
“…A competitive environment’s demands and resource scarcities (Connelly et al ., 2012; Chatterjee et al ., 2021) could foster a behavior causing healthcare professionals to amass knowledge without direct intent to obstruct the organization’s knowledge flows (Hammoda and Durst, 2022). Moreover, the view of knowledge as a source of power and psychological property in knowledge-dense settings (Peng, 2013) sets grounds to view knowledge hoarding as a protective strategy that positively impacts individual well-being in intense competition (Issac et al ., 2024).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second article, "True knowledge vs empowering knowledge: conceptualizing a theory of mindfulness and knowledge transfer (TMKT)," Issac et al (2024) explore the influence of mindfulness on different elements of knowledge management: knowledge creation, knowledge sharing and knowledge hiding using an inductive reasoning approach. They found that mindfulness enables an open environment and improves thought clarity, which helps in creating knowledge effectively.…”
Section: Guest Editorialmentioning
confidence: 99%